PEMBUATAN GAME BERBASIS PEMBELAJARAN MENGGUNAKAN RPG MAKER MV - Wahyuni, Sri Ngudi; Andiyoko, Cia (Journal of Computer Networks, Architecture and High Performance Computing, 2019)
The RPG game is one of the games are in great demand by the public because they are able to sharpen their right brain. One method used in game development is GDLC which consists of 6 phases, where each phase is arranged systematically. The aimed of this study is how to develop RPG maker game based learning for children cognitive. The analysis method is used SWOT analysis and testing method used ? and ? testing methods on 36 respondents who were taken by random and the response rate was 99.8%. The testing instrument used a questionnaire with testing parameters (1) Design consisting of music, sound, and color (2) Moral Message (3) Storyline. The test of results were 42.5% of respondents said that the development design was considered good, 44.3% of respondents said the game had a good storyline, and 56.3% of respondents stated that the Rise of the Zokai Clan game using RPG Maker MV had a good moral message.